The Effect of Breast Massage Education on Breast Milk Production in Postpartum Mothers in Lamamek Village, West Simeulue District, Simeulue Regency, Aceh Province - Ressi Yulisa; Dinah Khayyiriyah; Jannatil Ma'wa; Khairina; Hayatul Ridha (Athallah Publishing, 2026)
Breast milk is the best source of nutrition for babies which plays an important role in growth and development. However, there are still many postpartum mothers who experience obstacles in milk production, especially in the early postpartum period. One of the non-pharmacological efforts that can be made is breast mass education which aims to stimulate the hormones prolactin and oxytocin so that it can increase breast milk production. To determine the effect of breast mass education on breast milk production in postpartum mothers in Lamamek Village, West Simeulue District, Simeulue Regency, Aceh Province. This study uses a quasi-experimental design with a one group pretest-posttest design approach. The population in this study is all postpartum mothers as many as 52 people with a sampling technique, namely total sampling. Data collection was carried out through observation of breast milk production before and after the intervention. Data analysis was conducted using the Paired Sample T-Test. Results: The results of the study showed an increase in breast milk production after being given breast massage education. The average value of milk production before intervention was 14.85 ml and after intervention increased to 25.90 ml. The results of the statistical test showed a p value = 0.000 (p < 0.05), which means that there is a significant influence between breast mass education on breast milk production. There is an effect of breast mass education on increasing breast milk production in postpartum mothers in Lamamek Village, West Simeulue District, Simeulue Regency. Suggestion: It is hoped that health workers can increase education about breast mass to postpartum mothers as an effort to increase optimal breast milk production.